2017
DOI: 10.1002/mnfr.201700009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and biological function of milk‐derived miRNAs

Abstract: These results reinforce previous findings on the importance of miRNA in breast milk. Future studies should concentrate on the addition of miRNA to infant formulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
253
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(268 citation statements)
references
References 57 publications
7
253
0
4
Order By: Relevance
“…Golan‐Gerstl et al. have recently performed next‐generation sequencing and profiled different fractions of milk including milk from different species . Most strikingly, the authors co‐incubated the milk‐derived miRNAs with normal and cancer cells and observed increased quantity of miR‐148a and downregulation of a target gene.…”
Section: Discussionmentioning
confidence: 99%
“…Golan‐Gerstl et al. have recently performed next‐generation sequencing and profiled different fractions of milk including milk from different species . Most strikingly, the authors co‐incubated the milk‐derived miRNAs with normal and cancer cells and observed increased quantity of miR‐148a and downregulation of a target gene.…”
Section: Discussionmentioning
confidence: 99%
“…Among those, the same microRNAs are recurrently found in the top 10 most enriched sequences in milk (Table ). Most interestingly, in all the studies, these 10 microRNAs represent 40% to 80% of all sequences suggesting that, depending on the sample, a limited number of microRNA is specifically secreted in milk (Golan‐Gerstl et al., ; Kahn et al., ; Liao et al., ; Munch et al., ; Rubio et al., ; Simpson et al., ; van Herwijnen et al., ; Zhou et al., ).…”
Section: Micrornas In Milkmentioning
confidence: 99%
“…MicroRNA hsa‐miR‐148a‐3p is consistently the most abundant microRNA in breast milk, most likely because of its importance for lactation and its enrichment in mammary gland cells (Chen et al., ; Do, Dudemaine, Li, & Ibeagha‐Awemu, ; Gu et al., ; Muroya et al., ). It is then with little surprise that this microRNA is the most studied milk microRNA (Benmoussa et al., ; Golan‐Gerstl et al., ; Melnik, ; Melnik & Schmitz, , ; Simpson et al., ; van Herwijnen et al., ). Other less‐expressed microRNAs have nevertheless been investigated in breast milk, like the immunity‐related microRNAs hsa‐miR‐223 or hsa‐miR‐146a (Iannaccone et al., ; Liao et al., ; Perri et al., ; van Herwijnen et al., ).…”
Section: Micrornas In Milkmentioning
confidence: 99%
See 2 more Smart Citations